Proposed consensus definitions for new‐onset refractory status epilepticus (NORSE), febrile infection‐related epilepsy syndrome (FIRES), and related conditions. (5th February 2018) - Hirsch, Lawrence J.; Gaspard, Nicolas; van Baalen, Andreas; Nabbout, Rima; Demeret, Sophie; Loddenkemper, Tobias; Navarro, Vincent; Specchio, Nicola; Lagae, Lieven; Rossetti, Andrea O.; Hocker, Sara; Gofton, Teneille E.; et al.
Summary: We convened an international group of experts to standardize definitions of New‐Onset Refractory Status Epilepticus (NORSE), Febrile Infection‐Related Epilepsy Syndrome (FIRES), and related conditions. This was done to enable improved communication for investigators, physicians, families, patients, and other caregivers. Consensus definitions were achieved via email messages, phone calls, an in‐person consensus conference, and collaborative manuscript preparation. Panel members were from 8 countries and included adult and pediatric experts in epilepsy, electroencephalography (EEG), and neurocritical care. The proposed consensus definitions are as follows: NORSE is a clinical presentation, not a specific diagnosis, in a patient without active epilepsy or other preexisting relevant neurological disorder, with new onset of refractory status epilepticus without a clear acute or active structural, toxic or metabolic cause. FIRES is a subcategory of NORSE, applicable for all ages, that requires a prior febrile infection starting between 2 weeks and 24 hours prior to onset of refractory status epilepticus, with or without fever at onset of status epilepticus. Proposed consensus definitions are also provided for Infantile Hemiconvulsion‐Hemiplegia and Epilepsy syndrome (IHHE) and for prolonged, refractory and super‐refractory status epilepticus. This document has been endorsed by the Critical Care EEG Monitoring Research Consortium. We hope these consensus definitions will promote improved communication, permit multicenter research, and ultimately improve understanding and treatment of these conditions.